ANALISIS PROFITABILITAS PEMBANGUNAN PERUMAHAN PADA PT. SEJAHTERA LESTARI - Halmu, Muhammad (EKONOMIA, 2013)
Advantages acquisition is a very important tool for obtaining information regarding the financial position. To assess the financial performance of a business venture, required some specific benchmarks or standards. The standard can be either historical comparison or financial comparison with the financial data in the prior year period. Without such a comparison, will not be known whether the performance of a task force showed increased or decreased.From the description that has been previously described problems can be formulated as follows: "Analysis of Profitability Profit Housing Development on Sustainable PT.Sejahtera consisting Profitability ratio of 2010 to 2012 the average decline".Problem solving and hypothesis verification is done by analyzing the ratio of Pofitabilitas (Net Profit Margin, Return on Equity, Return on total assets), as well as the percentage per component analysis is done by comparing an item to the total in the same financial statements to calculate the growth and look at the financial performance PT.Sejahtera Lestari in 2010 until 2012.The analysis showed that there was a tendency on average improved financial performance PT.Sejahtera Lestari. Based on these explanations, the hypothesis is accepted, but not the case there is a tendency of decrease in the average profitability ratio that PT.Sejahtera Sustainable financial performance declined. Based on these explanations, the hypothesis is rejected.